GAMBARAN PENGETAHUAN PASIEN YANG AKAN DILAKUKAN ENDOSCOPY TENTANG MANFAAT ENDOSCOPY - PATONAH, SITI; ZUHRIYAH, AINU; Ika Irawan, Roesfida Dyah (Jurnal Penelitian Kesehatan, 2015)
ABSTRACT Endoscopy is a diagnostic support tool that is reliable. However, in patients hospitalized, endoscopy examination has not been widely known by the patient. Phenomena found in the field are still many families of patients who refuse to do an endoscopy examination because of their ignorance about the procedure, indications and benefits endoscopy. purpose this study was to determine the respondents awareness of the Benefits Of edoscopy Benefits Of endoscopy.             The study design used is descriptive research with a survey approach. The population was all patients prior to endoscopy which the sample was taken by using a non-probability sampling technique that is accidental sample, a number of 17 respondents. The research variables are patients knowledge about the benefits of endoscopy, then done editing, coding, scoring and tabulating then be deduced by using the percentage through descriptive analysis.             The result is more than the majority of respondents prior to endoscopy in Space Class B Hospital Endoscopy Dr R. Sosodoro Djatikoesoemo Bojonegoro in 2013 have less knowledge about the benefits of endoscopy at 58.82%. The conclusion of this study is the respondent must actively to seek out and gather information by asking questions and seek clarification on the health professionals about the procedure and the benefits of doing an endoscopy. Health workers should play an active role to provide information in the form of health education (health education) to patients who will do an endoscopy. Keywords:  Knowleydge, Patient And Endoscopy